2014
DOI: 10.1111/jpi.12148
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the time course of expression of the Nox family in the brain in a rat experimental cerebral ischemia and reperfusion model: effects of melatonin

Abstract: Ischemia–reperfusion (I/R) injury induces the generation of reactive oxygen species (ROS), which results in a poor prognosis for ischemic stroke patients. This study was designed to evaluate the time course of expression of the Nox family, a major source of ROS, and whether melatonin, a potent scavenger of ROS, influences these parameters in a rat model of cerebral I/R caused by middle cerebral artery occlusion (MCAO). After 2‐hr occlusion, the filament was withdrawn to allow reperfusion. At 0, 3, 6, 12, 24, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 35 publications
(59 reference statements)
3
50
0
1
Order By: Relevance
“…As described previously [32], we costained brain sections for CBS and NeuN or MST and NeuN to evaluate the expressions of CBS and 3MST in neurons. All the primary antibodies were applied at dilution of 1:100, and all the second antibodies were diluted at 1:500.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously [32], we costained brain sections for CBS and NeuN or MST and NeuN to evaluate the expressions of CBS and 3MST in neurons. All the primary antibodies were applied at dilution of 1:100, and all the second antibodies were diluted at 1:500.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Normal rabbit IgG was used as a negative control (data not shown). The fluorescence images were captured, and the relative fluorescence intensity was analyzed as described in our previous study [32].…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Additional studies revealed that NOX2 is primarily localized in neurons and endothelial cells at early time-points (3–6 h) after tGCI, followed by expression in microglial cells at later time-points (72 hr) [132, 134]. Likewise, studies in focal cerebral ischemia animal models also found that NOX2 and NOX4 mRNA and protein, as well as NOX activity are elevated in the peri-infarct region of the cerebral cortex from 2–48 h after reperfusion [135138]. Few studies have examined later time-points, but one study found NOX2 protein expression was markedly elevated in the peri-infarct region of the cortex up to 2 weeks after focal cerebral ischemia [139].…”
Section: Introductionmentioning
confidence: 99%
“…34 Unexpectedly, the upregulation of Nox4 was gradually induced and reached maximal levels at day 4 after brain ischemia, and was higher in pMCAO than in tMCAO (Figures 1b and c). Although there is a paper demonstrating the immediate upregulation of Nox4 after brain ischemia, 35 some papers have shown that Nox4 is significantly upregulated at 24 hours after MCAO in mice [36][37][38] . In particular, Kleinschnitz et al 36 demonstrated the significant upregulation of Nox4 in the cortex at later than 24 hours after brain ischemia.…”
Section: Brain Pericytes Express Nox4mentioning
confidence: 99%